PENGARUH POLA LATIHAN SIRKUIT TRAINING DAN LARI FARTLEK TERHADAP DAYA TAHAN AEROBIK ATLET PENCAK SILAT PAGAR NUSA - Yanwar Setiyo Putra; Ratno Susanto; Achmad Afandi (Jayabama: Jurnal Peminat Olahraga, 2023)
Monotonous pattern of aerobic exercise and lack of variation in aerobic exercise in pencak silat training. The purpose of this study was to determine the effect of circuit training and fartlek running on increasing the aerobic endurance of Pagar Nusa Pencak Silat athletes in Batu City. The results of the study are as follows, the results of the pre-test of the training circuit have the highest score of 40.5 and the lowest score of 21.8 with an average of 33.34 with a standard deviation of 6.67. While the fartlek run has the highest score of 34.3 and the lowest score of 27.9, the average data is 30.70 with a standard deviation of 2.36. The results of the post-test of the training circuit have the highest score of 44.5 and the lowest score of 28.3 with an average of 37.31 with a standard deviation of 5.83. Meanwhile, the fartlek run has the highest score of 37.8 and the lowest score of 30.2, with an average data of 34.35 with a standard deviation of 2.41. So that it can be seen that there is no significant difference in the effect between circuit training and flex running. Researchers provide suggestions. This research still needs to be further developed in the hope of providing more significant data as a comparison between circuit training treatment and fartlek running by adding more research subjects. With the addition of research subjects, it is expected to get more different data and get more significant differences in the results.